Protocol for in vivo dual-color fiber photometry in the mouse thalamus - Serikov, Almas; Iryna Martsishevska; Wooyeon Shin; Kim, Jeong jin (Elsevier, 2024)
In vivo calcium imaging of neural activity is an indispensable approach for understanding the mechanisms and functions of neural system. Development of advanced imaging tools and various genetically encoded calcium indicators allows us to simultaneously record the activity of different neural populations. Here, we present a protocol for acquiring neural activity of two discrete neural populations in mice using dual-color fiber photometry. We describe steps for injecting viral constructs and implanting the fiber optic through stereotaxic surgery, calcium signal acquisition, and data analysis. We also describe the incorporation of electroencephalogram and electromyography recordings with dual-color fiber photometry analysis.